Deafness and Theory of Mind Performance: Associations among Filipino Children, Adolescents, and Young Adults. Issue 3 (26th May 2020) - de Gracia, Ma. Regina Laya; de Rosnay, Marc; Hawes, David; Perez, Maria Veronica Templo
ABSTRACT: The acquisition of theory of mind (ToM) – the ability to attribute mental states to explain others' behaviors – is a critical milestone in children's cognitive development. Previous research has established that deaf children experience significant delays in ToM compared to hearing children within the same culture. However, prior studies were restricted due to the reliance on work in deaf samples from Western cultures. Thus, to examine the pattern and rate of acquisition of ToM in a non-Western context, the present study compares the performance of deaf and hearing groups from the Philippines. This research reports on two studies ( n = 209 and n = 42) that explore ToM performance among Filipino deaf and hearing individuals using a ToM scale. In study 1, deaf children aged 8 to 14 years demonstrated significant deficits in ToM relative to younger 3 to 7-year-olds and age-matched hearing controls. In study 2, a significantly greater proportion of deaf adolescents and young adults aged 15 to 22 years showed better ToM than the younger deaf group in study 1. Improved performance notwithstanding, the scores of the older deaf participants were still lower than those of the 8 to 14-year-old hearing children in study 1. Despite these delays, the pattern of ToM acquisition of both deaf and hearing Filipino groups mirrored that of Western cultures. Results are discussed in terms of the complex nature of communication within Filipino families and the limited access to conversations in families with deaf children.